(untitled) (Al-Academy, 2015)
Longer taboo one of the most dominant concepts in the artwork structure, especially the theatrical text as Achtgala bilateral awareness and presence to the overall transformations and secretions that affect the form discourse dramatic and therefore diversity in visions and methods according to the intellectual and aesthetic data that give rise to the culture of the individual and society alike. From the above point of crystallized privacy emerged from the research, including its chapters and discussing it